Medical expenditure growth and the diffusion of medical technology - Justin Polchlopek (The University of Utah, Department of Economics, 2011)
The general consensus among health economists is that the increasing capability of medical providers-often called medical technology-is responsible for the majority of growth in medical expenditure. And yet, the principle means of understanding medical technology is through the use of total factor productivity, which, despite giving reasonable estimates of the magnitude of the effects, is not a theory of technology, leaving policymakers without effective tools for prediction. This paper develops a descriptive model of technology that may have interesting implications for health economics. The model suggests that the manner of diffusion of technology is critical, and when technology diffuses haphazardly, the effects on expenditure can be unexpectedly large.
Keywords: B51; C67; D24; D57; I11; I12; O33; 330; Health Economics; Health Care Production; National Health Expenditures; Sraffian Economics; Total Factor Productivity; Input-Output Economics; Technological Diffusion Processes